DETERMINING THE EFFECTIVENESS OF IRRIGATION STANDARDS AND WATER-SAVING TECHNOLOGIES IN THE CULTIVATION OF LOCAL GRAPE VARIETIES (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
Water scarcity is a growing concern, and the agricultural sector must find ways to maximize water efficiency without compromising productivity. In recent years, numerous water-saving technologies have emerged, specifically designed for grape cultivation. These technologies offer promising solutions to reduce water usage and optimize irrigation. One such technology is moisture sensors, which provide real-time data on soil moisture levels. These sensors allow growers to monitor the water requirements of the vines and adjust irrigation practices accordingly. By avoiding over-irrigation, moisture sensors can significantly reduce water waste. Additionally, technologies like weather-based irrigation controllers use weather forecasts to adjust irrigation schedules, ensuring that water is only applied when necessary.